STRATEGI HARGA PADA PENENTUAN PAKET UMRAH DI PT RAIHANAH AWALIYAH MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
The main problem of this research is how the pricing strategy is in determining the Umrah package at PT Raihanah Awaliyah Makassar. In this research there are two problem formulations, namely (1) What is the pricing strategy for the Umrah package at PT Raihanah Awaliyah Makassar? (2) How are prospective pilgrims' responses to the pricing strategy for the Umrah package at PT Raihanah Awaliyah Makassar? This research uses a descriptive qualitative research type, which is conducted by looking for data directly in the field. This research uses a scientific approach to Hajj and Umrah management, especially regarding the pricing strategy in determining the Umrah package. The data sources used in this research are primary data sources and secondary data sources. Primary data sources are in the form of observation results, interviews with the president director, staff and prospective pilgrims of PT Raihanah Awaliyah Makassar and direct documentation from the field, while secondary data sources are in the form of data obtained from books, journals, the internet, literature, and other readings related to the research. The results of the study obtained that the pricing strategy for the Umrah package at PT Raihanah Awaliyah Makassar first used an adaptive strategy, where the package price was adjusted; cost-based pricing (based on operational costs); value-based pricing (based on the value given to consumers); price transparency to maintain customer trust; and pricing without fake discounts (non-promotional pricing) by not implementing fake discount strategies in its promotions. Travel confirms their commitment to integrity and fairness in pricing. Meanwhile, the response given by prospective pilgrims was very positive; by assessing the cheap price and good facilities, price transparency and satisfactory service, price comparisons, and recommendations from relatives (word of mouth), this has resulted in an increase in prospective pilgrims from year to year. The implications of this study are: 1) It is hoped that PT Raihanah Awaliyah Makassar will provide facilities for picking up pilgrims' luggage at their respective homes. 2) It is hoped that prospective pilgrims can be more careful in choosing each package offered and pay attention to the facilities of each package so that they can worship comfortably and be open with travel.